Optical coherence tomography angiography: A comprehensive review of current methods and clinical applications. (September 2017) - Kashani, Amir H.; Chen, Chieh-Li; Gahm, Jin K.; Zheng, Fang; Richter, Grace M.; Rosenfeld, Philip J.; Shi, Yonggang; Wang, Ruikang K.
Abstract: OCT has revolutionized the practice of ophthalmology over the past 10–20 years. Advances in OCT technology have allowed for the creation of novel OCT-based methods. OCT-Angiography (OCTA) is one such method that has rapidly gained clinical acceptance since it was approved by the FDA in late 2016. OCTA images are based on the variable backscattering of light from the vascular and neurosensory tissue in the retina. Since the intensity and phase of backscattered light from retinal tissue varies based on the intrinsic movement of the tissue (e.g. red blood cells are moving, but neurosensory tissue is static), OCTA images are essentially motion-contrast images. This motion-contrast imaging provides reliable, high resolution, and non-invasive images of the retinal vasculature in an efficient manner. In many cases, these images are approaching histology level resolution. This unprecedented resolution coupled with the simple, fast and non-invasive imaging platform have allowed a host of basic and clinical research applications. OCTA demonstrates many important clinical findings including areas of macular telangiectasia, impaired perfusion, microaneurysms, capillary remodeling, some types of intraretinal fluid, and neovascularization among many others. More importantly, OCTA provides depth-resolved information that has never before been available. Correspondingly, OCTA has been used to evaluate a spectrum of retinal vascular diseases including diabetic retinopathy (DR), retinal venous occlusion (RVO), uveitis, retinal arterial occlusion, and age-related macular degeneration among others. In this review, we will discuss the methods used to create OCTA images, the practical applications of OCTA in light of invasive dye-imaging studies (e.g. fluorescein angiography) and review clinical studies demonstrating the utility of OCTA for research and clinical practice. Highlights: OCTA images provide reliable, high resolution, and non-invasive images of retinal vascular tissue in a clinically feasible manner. OCTA demonstrates clinically significant features of diabetic retinopathy, retinal vein occlusion, macular degeneration, and glaucoma. Quantitative OCTA metrics show good correlation with clinical severity of diabetic retinopathy, retinal venous occlusion, and uveitis. Current FDA approved SD-OCTA systems have limited resolution underneath the RPE and a field-of-view that is limited to the macula. Current OCTA methods display and interpret data in a 2D manner. Advances in 3D rendering and wide-field metrics will provide more information.